Preparation and characterization of polymer‐Ti3C2Tx (MXene) composite nanofibers produced via electrospinning. Issue 37 (25th May 2017) - Mayerberger, Elisa A.; Urbanek, Olga; McDaniel, Riki M.; Street, Reva M.; Barsoum, Michel W.; Schauer, Caroline L.
ABSTRACT: MXene, a recently‐discovered family of two‐dimensional (2D) transition metal carbides and/or nitrides, have attracted much interest because of their unique electrical, thermal, and mechanical properties. In this study, poly(acrylic acid), poly(ethylene oxide) (PEO), poly(vinyl alcohol) (PVA), and alginate/PEO were electrospun with delaminated Ti3 C2 (MXene) flakes. The effect of small additions of delaminated Ti3 C2 (1% w/w) on the structure and properties of the nanofibers were investigated and compared with those of the neat polymer nanofibers using scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, and Fourier transform infrared spectroscopy. Ti3 C2 had an effect on the solution properties of the polymer and a greater effect on the average fiber diameter. The Ti3 C2 T x /PEO solution exhibited the largest change in viscosity and conductivity with an 11% and 73.6% increase over the base polymer, respectively. X‐ray diffractograms demonstrated a high degree of crystallization for Ti3 C2 /PEO and a slight decrease in crystallinity for Ti3 C2 /PVA. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45295. Abstract :